Implications of changes in land use for ecosystem service values of two highly eroded watersheds in Lake Abaya Chamo Sub-basin, Ethiopia - Mekuria, Wolde; Gedle, A.; Tesfaye, Y.; Phimister, E. (Elsevier, 2023)
Ecosystems provide a variety of ecosystem services and functions for mankind, and their sustainable use plays an important role in livelihoods. However, the resulting land degradation due to land use and land cover changes leads to loss of valuable ecosystems and associated ecosystem functions and services. This study takes two highly degraded watersheds, Aba-Bora and Guder, in Ethiopia and uses the value transfer valuation method to estimate changes in ecosystem service values. The study shows how loss of cropland and grazing lands can significantly affect ecosystem services even when plantations and shrubland increase. The results suggest that over a period of 41 years, the ecosystem service value of exclosures/shrublands and plantations increased, whereas that of crop and grazing lands decreased. The loss of ecosystem service values due to the decrease in cropland and grazing lands outweigh the gains due to the expansion of plantations and exclosures and resulted in a total loss of ecosystem service values of US$ 1.6 million in Aba-Bora watershed and US$ 24.4 million in Guder. In both watersheds, the greatest contributor to ecosystem service loss was a decline in supporting services, while the increase in plantation and shrublands (mainly through establishment of exclosures) meant that regulating ecosystem services suffered the smallest loss. Given their importance to livelihoods in these areas, the loss in crop and grazing lands significantly increase the vulnerability to shocks and narrow future livelihood options for many households. Given that severe gully erosion is the major contributor to the reduction in crop and grazing lands, catchment management that integrates the conservation of upstream areas using diverse sustainable land management practices, and gully rehabilitation measures in downstream areas could be an important option to reducing the expansion of big gullies, and conserving crop and grazing lands and ecosystem service values. However, the results suggest that the risks to livelihoods may be underestimated while the effectiveness of current actions to address land degradation over-estimated by communities.